Fenomena Pertemuan Dua Air Laut dalam Surat al-Rahman 19-20 - Nurjanah; Subini, Sri Suparsih; Patimatul Husna; Ahmad Mujahid (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
The Qur’an contains around 32 verses that discuss the sea, ocean, coast, estuary, and various other aquatic elements. This fact is truly astonishing, considering that the holy book was revealed in a desert region far from the sea, and there are no records indicating that any revelation occurred in the middle of the ocean. One of the extraordinary phenomena revealed in the Qur’an is the meeting of two seas that do not mix with each other. Even before modern science discovered it, the Qur’an had already disclosed the existence of this phenomenon. Interestingly, the existence of these two distinct bodies of water was only identified in modern times, and to this day, the phenomenon continues. Research in modern physics and chemistry has confirmed the reality of this natural event as described in the Qur’an. These findings further affirm that the information contained in the Qur’an hundreds of years ago aligns with the results of contemporary scientific research. Thus, the verse discussing the meeting of two seas not only illustrates a natural wonder but also demonstrates that there is no contradiction between science and the Qur’an Keywords: Al-Qur’an, Sea, Scientific